Design of a Reciprocating Manual Weed Cutter for Hill Orchard - Mandal, S.; Kumar, Arvind; Singh, R. K. (Journal of Agricultural Engineering, 2014)
Cutting of weeds in hill orchards is labour and time intensive. When performed with grass slasher or traditional dao through impact cutting, it consumes approximately 50% of total labour requirement for cultivation. A simple and low-cost reciprocating weed cutter was designed with a cutter bar width of 600 mm. It consists of a handle, frame, reciprocating cutter bar, tension wire, spring and two wheels. Actual field capacity and field efficiency of the equipment were 0.60 ha.day-1 and 86.36%, respectively, which were higher than traditional dao and hand grass slasher. Energy expenditure with the reciprocating grass cutter (27.1 kJ.min-1) was 42.72% lesser than dao and 37.55% than grass slasher, respectively.